A polyolefin composition and its preparation method and application

By using PE, PP, EPM and EPDM blends in photovoltaic cable insulating materials, and adding paraffin oil and oleic acid amide as release agents in the preparation process, the problem of slow production speed and easy to cause messy lines is solved, and efficient production and easy peeling effect is achieved.

CN116396550BActive Publication Date: 2025-04-18SUZHOU CPLUS NEW MATERIAL
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211596825.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-12
Publication Date
2025-04-18
Estimated Expiration
2042-12-12

AI Technical Summary

Technical Problem

During the production process, existing photovoltaic cable insulation materials have problems such as slow production speed, easy bulge insulating materials, difficult peeling, and easy chaotic wire laying, resulting in a decrease in production efficiency and component assembly efficiency, resulting in a large amount of scrapping.

Method used

A blend of polyethylene (PE), polypropylene (PP), ethylene propylene binary rubber (EPM) and ethylene propylene ternary rubber (EPDM) is used, and paraffin oil and oleic acid amide are added as release agents in different preparation processes. By controlling the rheological properties and cross-linking process of the material, the peelability and production efficiency of the insulating material are improved.

Benefits of technology

It realizes efficient production and easy peeling effect of photovoltaic cable insulation materials, solves the problems of messy wires and bulging during the production process, and improves the mechanical performance and assembly convenience of the cable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a polyolefin composition and a preparation method and application thereof. The raw materials of the polyolefin composition comprise, by weight percentage, 40%-70% of polyethylene, 10%-33% of polypropylene, 5%-10% of ethylene propylene rubber, 6%-10% of ethylene propylene rubber, 1%-3% of a release agent, 2.5%-3.5% of a crosslinking agent and other additives, wherein the release agent is composed of paraffin oil and oleic acid amide. The preparation method comprises the following steps: mixing polyethylene, ethylene propylene rubber, ethylene propylene rubber, a crosslinking agent and part of other additives, performing banburying and extruding, then adding polypropylene, paraffin oil and the remaining other additives, mixing and evenly mixing, extruding, and mixing the obtained particles with oleic acid amide and extruding. The polyolefin composition of the invention can be used as an insulating material for an insulating layer of a photovoltaic cable, is not only easy to be stripped and not prone to tangled lines during extrusion, but also has good processing performance, high production efficiency and simple and readily available raw materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photovoltaic cables, in particular to an easily strippable photovoltaic cable insulation layer, and specifically to a polyolefin composition and a preparation method and application thereof. The polyolefin composition can be cross-linked by radiation and can achieve easy stripping, easy wire laying, easy processing, etc. Background Art

[0002] As the concepts of green, environmental protection, and sustainable development have become more popular and in response to global warming, the global demand for green energy has increased significantly, and photovoltaic power generation is an important part of it. As an indispensable part of the photovoltaic power generation system, the market demand for photovoltaic cables has continued to increase with the booming photovoltaic market. Although photovoltaic cables are not the core components of the photovoltaic industry, they are an indispensable component for connecting various photovoltaic parts and transmitting electrical energy. Therefore, the localization of photovoltaic cable materials is of great significance to further improve the competitiveness of the photovoltaic industry.

[0003] Photovoltaic cables are generally composed of three parts: conductor, insulation layer and sheath. In order to meet the requirements of UL (US product safety testing and certification agency) standards, the insulating material of the insulation layer is generally modified by adding lubricants and other additives to the PE substrate. Among them, the process performance, rigidity and adhesion of the PE substrate have a decisive influence on the performance of the finished insulation material, and then affect the production of photovoltaic cables and the assembly of wiring harness components. It is understood that a well-known domestic photovoltaic cable material manufacturer uses easy-to-process PE produced in Japan, which has achieved a balance of various properties of insulation materials to a certain extent and has been widely used in photovoltaic cables. The supply of Japanese raw materials suitable for photovoltaic cable insulation is in short supply and the price has risen sharply. It can no longer be used in photovoltaic insulation materials. When other brands of PE are used as the substrate, it is found that the cable production speed is slow, the insulation material is easy to bulge, not easy to peel, and the wire reel is easy to mess up. Problems such as the production efficiency of photovoltaic cables and the assembly efficiency of components have not only greatly reduced, but also caused a large number of scraps, causing significant losses to related companies, and seriously affecting production capacity and delivery. Summary of the invention

[0004] The purpose of the present invention is to overcome one or more deficiencies in the prior art and provide a new polyolefin composition capable of radiation cross-linking, which can be used as an insulating material for the insulating layer of a photovoltaic cable, is not only easy to peel and not prone to tangled wires during extrusion, but also has good processing performance and high production efficiency.

[0005] The present invention also provides a method for preparing the polyolefin composition.

[0006] The present invention also provides a use of the polyolefin composition in preparing an insulating layer for a photovoltaic cable.

[0007] The inventors of the present invention have conducted intensive research on the problems existing in the production and use of photovoltaic cables. The research and analysis found that although the addition of commonly used release agents can improve the strippability of PE-based insulating materials to a certain extent, the effect still needs to be improved, and the strippability effect is unstable, with large differences between batches. At the same time, there is also the problem of disorderly laying out of insulating materials, which is not easy to lay out in an orderly manner, especially the production efficiency is low, which is not conducive to improving production capacity.

[0008] Furthermore, the inventors of the present invention have unexpectedly discovered through a large number of experiments that by blending PE, PP, EPM, and EPDM and further controlling the amount of PP added, especially by successively adding paraffin oil and oleamide in different preparation steps, not only the rheological properties of the material are solved and the production efficiency is improved, but also orderly release can be achieved, and a surprisingly easy-to-peel effect is obtained.

[0009] In order to achieve the above object, a technical solution adopted by the present invention is:

[0010] A polyolefin composition, the raw materials of which include polyethylene (PE), polypropylene (PP), ethylene propylene diene monomer (EPM), ethylene propylene diene monomer (EPDM), and an additive, wherein the additive includes a release agent and a crosslinking agent, and the release agent is composed of paraffin oil and oleic acid amide;

[0011] In terms of mass percentage, the raw materials include 40%-70% polyethylene, 10%-33% polypropylene, 5%-10% EPDM rubber, 6%-10% EPDM rubber, 1-3% release agent, and 2.5%-3.5% crosslinking agent;

[0012] The preparation method of the polyolefin composition comprises:

[0013] The polyethylene, EPDM rubber, EPDM rubber, and some additives except the release agent are mixed, kneaded, and extruded to obtain a first semi-finished product;

[0014] The first semi-finished product, polypropylene, paraffin oil, and the remaining additives except the release agent are mixed and extruded to obtain a second semi-finished product;

[0015] The second semi-finished product is mixed with oleamide and extruded.

[0016] According to some preferred aspects of the present invention, the mass ratio of the paraffin oil to the oleamide is 1:0.1-0.5.

[0017] According to some preferred aspects of the present invention, the mass ratio of the polyethylene, the polypropylene, the EPDM rubber, the EPDM rubber and the release agent is 20-40:3-33:1.5-10:2-10:1.

[0018] According to some preferred aspects of the present invention, the feed mass ratio of the EPDM rubber to the EPDM rubber is 0.8-1:1.

[0019] According to some preferred and specific aspects of the present invention, the raw material further comprises 2%-3% of antioxidant and 0.4%-0.6% of pigment, calculated by mass percentage.

[0020] According to some preferred aspects of the present invention, the polyethylene is a linear low-density polyethylene having a melt index of 0.1-1 g / 10 min.

[0021] According to some preferred aspects of the present invention, the polypropylene is a homopolypropylene having a melt index of 0.5-3 g / 10 min.

[0022] According to some preferred aspects of the present invention, the Mooney viscosity of the EPDM rubber is 10-50.

[0023] In the present invention, the Mooney viscosity of the EPDM rubber is measured at (ML1+4) and 100°C.

[0024] In the present invention, the melt index of polyethylene is measured at a temperature of 190° C. and a load of 2.16 kg, and the melt index of polypropylene is measured at a temperature of 230° C. and a load of 2.16 kg.

[0025] According to some preferred aspects of the present invention, the EPDM rubber is a copolymer of ethylene, propylene and non-conjugated diene, and the non-conjugated diene accounts for 3%-6% based on the total mass of ethylene, propylene and non-conjugated diene.

[0026] In some embodiments of the present invention, the non-conjugated diene may be ethylidene norbornene (ENB), dicyclopentadiene (DCPD), 1,4-hexadiene (HD), and the like.

[0027] According to some preferred aspects of the present invention, the antioxidant is a complex of antioxidant 1010, antioxidant DLTP, antioxidant 168 and a metal ion passivator.

[0028] According to some preferred and specific aspects of the present invention, the feed mass ratio of the antioxidant 1010, the antioxidant DLTP, the antioxidant 168 and the metal ion passivator is 1:0.5-0.7:0.5-0.7:0.3-0.4.

[0029] According to some preferred and specific aspects of the present invention, the metal ion passivator includes antioxidant 1024 and / or antioxidant XL-1.

[0030] In some embodiments of the present invention, the crosslinking agent is triallyl isocyanurate (TAIC) and / or trimethylolpropane trimethacrylate (TMPTMA).

[0031] Another technical solution provided by the present invention is a method for preparing the polyolefin composition described above, the method comprising:

[0032] (1) mixing polyethylene, EPDM rubber, EPDM rubber, and some additives except the release agent, kneading, and extruding to obtain a first semi-finished product;

[0033] (2) mixing the first semi-finished product, polypropylene, paraffin oil, and the remaining additives except the release agent, and extruding to obtain a second semi-finished product;

[0034] (3) The second semi-finished product and oleic acid amide are mixed and extruded.

[0035] According to some preferred aspects of the present invention, in step (1), the mixing temperature is 140-160°C, and the extrusion is performed by twin-screw and single-screw extrusion granulation, the twin-screw temperature is 110-150°C, and the single-screw temperature is 110-140°C.

[0036] According to some preferred aspects of the present invention, in step (2) and step (3), the extrusion is performed by twin-screw extrusion, and the temperature of the twin-screw is 120-200°C.

[0037] Another technical solution provided by the present invention is a use of the polyolefin composition described above in preparing an insulating layer for a photovoltaic cable.

[0038] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0039] The present invention is based on the problems existing in the existing use of commonly used polyethylene substrates to prepare photovoltaic insulation materials, such as slow cable production speed, easy bulging of insulation materials, difficulty in peeling, and easy disorder of wires on the pay-off reel. The present invention innovatively adopts a technical solution combining polypropylene, a release agent and materials with a cable preparation process, which solves the problem of high adhesion and difficulty in peeling. The present invention has high production efficiency and good mechanical (mechanical) properties, can realize orderly pay-off, and is convenient for the assembly of cables when used in photovoltaic power generation systems.

[0040] In addition, the product of the present invention can use all domestic raw materials, which are easy to obtain and have a stable supply. It also has good electrical insulation performance, process performance, and stripping performance. There are no process problems such as tangled lines and bulging during the production process. In the context of unstable supply of raw materials in the market and increasing demand in the photovoltaic market, it has significant economic and market benefits. DETAILED DESCRIPTION

[0041] The main concepts of the present invention are: (1) creatively using PP as a resin blend. The inventors have found that the addition of PP can not only improve the rheological properties of the formulation system of the present invention, but also avoid the phenomenon that the melt fracture of some polyethylene causes the extrudate to form a screw-like surface, thereby improving the cable production speed and production efficiency and reducing the manufacturing cost of the enterprise. Moreover, when the addition amount is within a specific range, the area occupied by PP in the insulating material is increased, and thus when used as an insulating material, it can fully contact with the conductor of the photovoltaic cable. Experimental verification shows that the insulating material is endowed with better release properties, and the problems of difficult cross-linking and excessive rigidity of the finished product can be avoided.

[0042] (2) Oleic acid amide and paraffin oil are added to the formula system. Although the compound release agent system is a compound system, it is added separately during use. Specifically, during the preparation process, paraffin oil and other components are first blended and extruded into granules. First, the paraffin oil is first wetted and adsorbed on the substrate under high temperature, shear and pressure conditions, thereby reducing the solubility of oleic acid amide in the substrate. Second, paraffin oil has good compatibility with the polyolefin substrate and has a certain swelling effect on the substrate. At the same time, it increases the mobility of the substrate chain segments, which is beneficial to the migration of oleic acid amide. Third, the crystalline part of the substrate will melt at high temperature and can accommodate more than the crystalline state. Paraffin oil, when cooled and recrystallized, the paraffin oil in the crystal area will be squeezed out, driving oleic acid amide to migrate outward; these three aspects are conducive to improving the migration ability, migration speed, and migration amount of oleic acid amide, so that it can quickly enrich between the conductor and the insulating material layer of the photovoltaic cable, reduce the adhesion of the insulating layer, and facilitate stripping; after the cable insulation extrusion process is completed, it will also go through the sheathing process, irradiation process, short-term placement until the stripping assembly, during which time the release agent can quickly migrate between the insulating material layer and the conductor, play a role in lubrication and reducing adhesion, while the current conventional release agent and its use method are characterized by slow migration speed, and cannot complete sufficient migration before assembly, and it is difficult to play a sufficient role in lubrication and reducing adhesion;

[0043] (3) Further combining with ethylene propylene diene monomer (EPM) and ethylene propylene diene monomer (EPDM), on the one hand, can better solve the problem of system compatibility and keep the performance of the material stable for a long time; on the other hand, it can further reduce the rigidity of the system, solve the problem of excessive rigidity of the system material, reduce the tension of the insulating core, and help solve the problem of disordered wires in the sheathing process.

[0044] Based on this, the present invention proposes a polyolefin composition, the raw materials of which include polyethylene (PE), polypropylene (PP), ethylene propylene diene monomer (EPM), ethylene propylene diene monomer (EPDM), and an additive, wherein the additive includes a release agent and a cross-linking agent, and the release agent is composed of paraffin oil and oleic acid amide;

[0045] In terms of mass percentage, the raw materials include 40%-70% polyethylene, 10%-33% polypropylene, 5%-10% EPDM rubber, 6%-10% EPDM rubber, 1%-3% release agent, and 2.5%-3.5% cross-linking agent;

[0046] The preparation method of the polyolefin composition comprises:

[0047] The polyethylene, EPDM rubber, EPDM rubber, and some additives except the release agent are mixed, kneaded, and extruded to obtain a first semi-finished product;

[0048] The first semi-finished product, polypropylene, paraffin oil, and the remaining additives except the release agent are mixed and extruded to obtain a second semi-finished product;

[0049] The second semi-finished product is mixed with oleamide and extruded.

[0050] Further, polyethylene is divided into low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), high-density polyethylene (HDPE), etc. The present invention preferably uses linear low-density polyethylene (LLDPE), which is not only low in cost, but also generally contains less long chain branches, but contains some short chain branches. The presence of short chain branches not only increases the gap between molecular chains, but also enhances the mobility of the molecular chain segments of the substrate, which is beneficial to the diffusion and migration of the specific release agent system of the present invention. At the same time, linear low-density polyethylene also has a higher degree of crystallinity, so its strength is better than that of low-density polyethylene, but its rigidity is lower than that of high-density polyethylene. Low-density polyethylene generally has relatively more and longer chain branches, and the long-chain branched structure is not conducive to the diffusion and migration of the specific release agent system of the present invention. High-density long chain branches and short chain branches are less, with high crystallinity, high strength, and high rigidity. Therefore, linear low-density polyethylene (LLDPE) is preferably used, and further, a linear low-density polyethylene with a melt index of 0.1-1g / 10min measured at a temperature of 190°C and a load of 2.16kg is used.

[0051] Furthermore, PP is preferably a homopolymer product, which has been shown in practice to have better release properties and lower melt strength. Furthermore, in the present invention, when the PP melt index is too small, it will lead to excessive current; when the PP melt index is too large, the melt index of the finished product will become larger, that is, the fluidity of the finished product will be too large, and more of the insulating layer will be squeezed into the gap of the twisted conductor, resulting in an increase in the contact area between the insulating layer and the conductor, and the adhesion will increase accordingly, causing difficulty in peeling. Therefore, the present invention selects homopolymer polypropylene with a melt index of 0.5-3g / 10min measured at a temperature of 230°C and a load of 2.16kg.

[0052] Furthermore, EPDM has good flexibility. Its addition can reduce the rigidity of the finished product and prevent the problem of disordered lines in the sheath extrusion process. In particular, the unsaturated components in its molecules can improve the mobility of its chain segments, which is beneficial to the diffusion and migration of the release agent of the present invention. Furthermore, the inventors have found that if the amount of EPDM added is too much, the finished product will be more easily cross-linked, the radiation dose will be small, and it will not be easy to be consistent with the radiation dose of the sheath material, resulting in inconsistent cross-linking degree. Therefore, the present invention selects EPDM with a third monomer (non-conjugated diene) content of 3%-6%.

[0053] Furthermore, in order to balance the radiation crosslinking of the insulation layer and the sheath layer, EPM and EPDM are mixed, which can not only fully reduce the rigidity of the insulation layer, but also solve the problem of large radiation dose deviation between the insulation and the sheath caused by excessive addition of EDPM. The Mooney viscosity is preferably 10-50.

[0054] Furthermore, the present invention uses oleamide and paraffin oil in combination, but they are added in different processes. Practice shows that in the system of the present invention, small molecule additives with flat or elongated molecules with smaller molecular weight are easier to diffuse than spherical molecules. Oleamide has a molecular weight of only about 281.477 and a melting point of about 72-77°C. At the same time, the molecule also contains unsaturated components, and the migration speed is relatively fast. In addition, during the cable irradiation process, the cable will be significantly heated due to the irradiation of the high-energy electron beam, and even reach above the melting point of oleamide. The melted oleamide is easier to diffuse and migrate, and the addition of paraffin oil can further ensure that oleamide completes sufficient migration before assembly to ensure release.

[0055] The above scheme is further described below in conjunction with specific embodiments; it should be understood that these embodiments are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following embodiments; the implementation conditions adopted in the embodiments can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in conventional experiments.

[0056] Unless otherwise specified in the following examples, all raw materials are commercially available or prepared by conventional methods in the art.

[0057] Example 1

[0058] This example provides a polyolefin composition and a preparation method thereof. The raw materials of the polyolefin composition include, by weight percentage: LLDPE 40%, PP 33%, EPM 10%, EPDM 10%, release agent 1%, antioxidant 3%, cross-linking agent 2.5%, pigment 0.5%;

[0059] LLDPE, linear low-density polyethylene, purchased from Shanghai Yiqing Trading Co., Ltd., brand ML2202, melt index 0.3 g / 10 min;

[0060] PP, homopolymer polypropylene, purchased from Suzhou Suge New Material Technology Co., Ltd., brand EH-01, melt index 0.8 g / 10 min;

[0061] EPM, ethylene propylene diene rubber, purchased from Shanghai Dinggong Rubber Co., Ltd., brand J-0050, Mooney viscosity 50;

[0062] EPDM, ethylene propylene diene monomer, purchased from Shanghai Dinggong Rubber Co., Ltd., brand J-3080, non-conjugated diene (third monomer) accounts for 5%;

[0063] The release agent is composed of paraffin oil and oleic acid amide, and the mass ratio of paraffin oil to oleic acid amide is 1:0.5; paraffin oil is purchased from Suzhou Saipahan Special Oil Co., Ltd., brand 150BS; oleic acid amide is purchased from Jiangxi Dongyuan Technology Co., Ltd., brand DY1618;

[0064] The antioxidant is a complex of antioxidant 1010, antioxidant DLTP, antioxidant 168 and metal ion passivator, the metal ion passivator is antioxidant 1024, and the feed mass ratio of antioxidant 1010, antioxidant DLTP, antioxidant 168 and metal ion passivator is 1:0.7:0.7:0.4;

[0065] Antioxidant 1010, antioxidant DLTP, antioxidant 168, and antioxidant 1024 were purchased from Beijing Jiyi Chemical Co., Ltd.;

[0066] The cross-linking agent is triallyl isocyanurate (TAIC);

[0067] The pigment is titanium dioxide, purchased from Shanghai Fumao Chemical Co., Ltd., with a brand number of 1812.

[0068] The preparation method of the polyolefin composition comprises:

[0069] Linear low-density polyethylene, EPDM rubber, EPDM rubber, antioxidant and cross-linking agent are weighed in proportion, added into an internal mixer and internally kneaded to 140°C, and then extruded and granulated by twin screw and single screw, and cooled to obtain the first semi-finished product; the temperature of the twin screw is: 110°C for zone 1, 120°C for zone 2, 130°C for zone 3, 140°C for zone 4, 150°C for zone 5, 150°C for zone 6 and 145°C for zone 7; the temperature of the single screw is: 110°C for zone 1, 120°C for zone 2, 130°C for zone 3, 140°C for zone 4, 135°C for zone 5, and 135°C for die head;

[0070] Then the first semi-finished product is mixed evenly with homopolymer polypropylene, paraffin oil and pigment according to a proportion, and then added into a twin-screw hopper, and subjected to twin-screw extrusion, water cooling, air drying and granulation to obtain a second semi-finished product; the temperature of each zone of the twin-screw is: 120° C. for zone 1, 135° C. for zone 2, 145° C. for zone 3, 155° C. for zone 4, 165° C. for zone 5, 170° C. for zone 6, 175° C. for zone 7, 180° C. for zone 8, 185° C. for zone 9, 190° C. for zone 10, 195° C. for zone 11, 200° C. for zone 12, 200° C. for zone 13, and 200° C. for the die head;

[0071] Then the second semi-finished product and oleic acid amide are mixed in proportion, and granulated according to the process of the second semi-finished product to obtain a finished product. The material properties are shown in Table 1.

[0072] Example 2

[0073] This example provides a polyolefin composition and a preparation method thereof. The raw materials of the polyolefin composition include, by weight percentage: LLDPE 55%, PP 22%, EPM 7%, EPDM 8%, release agent 2%, antioxidant 2.5%, crosslinking agent 3%, pigment 0.5%;

[0074] LLDPE, linear low-density polyethylene, purchased from Shanghai Langyue International Trading Co., Ltd., brand 9085, melt index 0.7 g / 10 min;

[0075] PP, homopolymer polypropylene, purchased from Suzhou Suge New Material Technology Co., Ltd., brand F200, melt index 2.0 g / 10 min;

[0076] EPM, ethylene propylene rubber, purchased from Shanghai Dinggong Rubber Co., Ltd., brand J-0030, Mooney viscosity 30;

[0077] EPDM, ethylene propylene diene monomer, purchased from Shanghai Dinggong Rubber Co., Ltd., brand J-2080, non-conjugated diene (third monomer) accounts for 3%;

[0078] The release agent is composed of paraffin oil and oleic acid amide, and the mass ratio of paraffin oil to oleic acid amide is 1:0.2; paraffin oil is purchased from Suzhou Saipahan Special Oil Co., Ltd., brand 150BS; oleic acid amide is purchased from Jiangxi Dongyuan Technology Co., Ltd., brand DY1618;

[0079] The antioxidant is a complex of antioxidant 1010, antioxidant DLTP, antioxidant 168 and metal ion passivator, the metal ion passivator is antioxidant XL-1, and the feed mass ratio of antioxidant 1010, antioxidant DLTP, antioxidant 168 and metal ion passivator is 1:0.6:0.6:0.4;

[0080] Antioxidant 1010, antioxidant DLTP, antioxidant 168, and antioxidant XL-1 were purchased from Beijing Jiyi Chemical Co., Ltd.;

[0081] The crosslinking agent is trimethylolpropane trimethacrylate (TMPTMA);

[0082] The pigment is titanium dioxide, purchased from Shanghai Fumao Chemical Co., Ltd., with a brand number of 1812.

[0083] The preparation method of the polyolefin composition comprises:

[0084] Linear low-density polyethylene, EPDM rubber, EPDM rubber, antioxidant and cross-linking agent are weighed in proportion, added into an internal mixer and internally kneaded to 150° C., then extruded and granulated by twin screw and single screw, and cooled to obtain the first semi-finished product; the temperature of the twin screw is: 110° C. for zone 1, 120° C. for zone 2, 130° C. for zone 3, 140° C. for zone 4, 150° C. for zone 5, 150° C. for zone 6, and 145° C. for zone 7; the temperature of the single screw is: 110° C. for zone 1, 120° C. for zone 2, 130° C. for zone 3, 140° C. for zone 4, 135° C. for zone 5, and 135° C. for the die head;

[0085] Then the first semi-finished product is mixed evenly with homopolymer polypropylene, paraffin oil and pigment in proportion, and then added into a twin-screw hopper, and the second semi-finished product is obtained through twin-screw extrusion, water cooling, air drying and granulation; the temperature of each zone of the twin screw is: 120°C in zone 1, 135°C in zone 2, 145°C in zone 3, 155°C in zone 4, 165°C in zone 5, 170°C in zone 6, 175°C in zone 7, 180°C in zone 8, 185°C in zone 9, 190°C in zone 10, 195°C in zone 11, 200°C in zone 12, 200°C in zone 13, and 200°C in the die head.

[0086] Then the second semi-finished product and oleic acid amide are mixed in proportion, and granulated according to the process of the second semi-finished product to obtain a finished product. The material properties are shown in Table 1.

[0087] Example 3

[0088] This example provides a polyolefin composition and a preparation method thereof. The raw materials of the polyolefin composition include, by weight percentage: LLDPE 70%, PP 10%, EPM 5%, EPDM 6%, release agent 3%, antioxidant 2%, crosslinking agent 3.5%, pigment 0.5%;

[0089] LLDPE, linear low-density polyethylene, purchased from Shanghai Langyue International Trading Co., Ltd., brand DFDA-6010, melt index of 0.95 g / 10 min;

[0090] PP, homopolymer polypropylene, purchased from Suzhou Suge New Material Technology Co., Ltd., brand S1003, melt index 3g / 10min;

[0091] EPM, ethylene propylene rubber, purchased from Shanghai Dinggong Rubber Co., Ltd., brand J-0010, Mooney viscosity 10;

[0092] EPDM, ethylene propylene diene monomer, purchased from Shanghai Dinggong Rubber Co., Ltd., brand J-3092E, non-conjugated diene (third monomer) accounts for 5.6%;

[0093] The release agent is composed of paraffin oil and oleic acid amide, and the mass ratio of paraffin oil to oleic acid amide is 1:0.1; the paraffin oil is purchased from Suzhou Saipahan Special Oil Co., Ltd., with the brand name 150BS; the oleic acid amide is purchased from Jiangxi Dongyuan Technology Co., Ltd., with the brand name DY1618;

[0094] The antioxidant is a complex of antioxidant 1010, antioxidant DLTP, antioxidant 168 and metal ion passivator, the metal ion passivator is antioxidant 1024, and the feed mass ratio of antioxidant 1010, antioxidant DLTP, antioxidant 168 and metal ion passivator is 1:0.5:0.5:0.3;

[0095] Antioxidant 1010, antioxidant DLTP, antioxidant 168, and antioxidant 1024 were purchased from Beijing Jiyi Chemical Co., Ltd.;

[0096] The cross-linking agent is triallyl isocyanurate (TAIC);

[0097] The pigment is titanium dioxide, purchased from Shanghai Fumao Chemical Co., Ltd., with a brand number of 1812.

[0098] The preparation method of the polyolefin composition comprises:

[0099] Linear low-density polyethylene, EPDM rubber, EPDM rubber, antioxidant and cross-linking agent are weighed in proportion, added into an internal mixer and internally kneaded to 160° C., then extruded and granulated by twin screw and single screw, and cooled to obtain the first semi-finished product; the temperature of the twin screw is: 110° C. for zone 1, 120° C. for zone 2, 130° C. for zone 3, 140° C. for zone 4, 150° C. for zone 5, 150° C. for zone 6, and 145° C. for zone 7; the temperature of the single screw is: 110° C. for zone 1, 120° C. for zone 2, 130° C. for zone 3, 140° C. for zone 4, 135° C. for zone 5, and 135° C. for the die head;

[0100] Then the first semi-finished product is mixed evenly with homopolymer polypropylene, paraffin oil and pigment in proportion, and then added into a twin-screw hopper, and the second semi-finished product is obtained through twin-screw extrusion, water cooling, air drying and granulation; the temperature of each zone of the twin screw is: 120°C in zone 1, 135°C in zone 2, 145°C in zone 3, 155°C in zone 4, 165°C in zone 5, 170°C in zone 6, 175°C in zone 7, 180°C in zone 8, 185°C in zone 9, 190°C in zone 10, 195°C in zone 11, 200°C in zone 12, 200°C in zone 13, and 200°C in the die head.

[0101] Then the second semi-finished product and oleic acid amide are mixed in proportion, and granulated according to the process of the second semi-finished product to obtain a finished product. The material properties are shown in Table 1.

[0102] Comparative Example 1

[0103] The method is basically the same as Example 1, except that PP is not added and LLDPE is adjusted to 73%.

[0104] Comparative Example 2

[0105] It is basically the same as Example 1, except that the addition amount of PP is 40% and the LLDPE is adjusted to 33%.

[0106] Comparative Example 3

[0107] The method is basically the same as Example 1, except that during the preparation process, paraffin oil and oleic acid amide are added together, mixed with the first semi-finished product, and then added to the twin-screw hopper, and the finished product is obtained through twin-screw extrusion, water cooling, air drying, and granulation.

[0108] Performance Testing

[0109] The following performance tests were performed on the finished materials obtained in the above-mentioned Examples 1-3 and Comparative Examples 1-3. The specific results are shown in Table 1; wherein, density and hardness are the test results before material irradiation, and tensile strength and adhesion are the test results after the cable is irradiated with a radiation dose of 15M.

[0110] The density of the finished product is tested in accordance with standard GB / T 1033, the hardness is tested in accordance with standard GB / T 2411, the tensile property is tested in accordance with standard GB / T 1040, and the adhesion is tested in accordance with standard GB / T 25085.

[0111] Table 1

[0112]

[0113] Wire disorder: In the present invention, wire disorder refers to the situation that during the cable production process, the core wire on the wire drum has too much tension. Under the condition of active wire release, due to the excessive rigidity of the core wire, the core wire spreads faster than the wire take-up speed, resulting in unstable tension and product outer diameter. In severe cases, the core wires may cross and misalign, resulting in the core wires being knotted or broken, and eventually having to stop the machine. Therefore, wire disorder will cause more defective products and scrap, affecting efficiency and cost.

[0114] Referring to Table 1, it can be seen from the comparison between Comparative Example 1 and Example 1 that without adding polypropylene, not only is the strippability poor, but the extrusion speed is greatly reduced; from the comparison between Comparative Example 2 and Example 1, it can be seen that when the amount of polypropylene added is too large, although the strippability is good, the toughness is poor, and the cable production process will also cause disordered lines, which has a serious negative impact on continuous production; from the comparison between Comparative Example 3 and Example 1, it can be seen that for the release agent of the present invention, when paraffin oil and oleic acid amide are added to the system together, not only does it not contribute to the strippability, but it also greatly reduces the strippability and makes stripping difficult; and the present invention, by blending PE, PP, EPM, and EPDM, further controls the amount of PP added, especially by successively adding paraffin oil and oleic acid amide in different preparation processes, not only solves the rheological properties of the material and improves the production efficiency, but also can achieve orderly wire laying, and also obtains a surprising easy-to-strip effect.

[0115] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

[0116] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

Claims

1. A polyolefin composition, whose raw materials include polyethylene and an additive, characterized in that: The raw materials also include polypropylene, EPDM rubber and EPDM rubber, and the additives include a release agent and a cross-linking agent, wherein the release agent is composed of paraffin oil and oleic acid amide; In terms of mass percentage, the raw materials include 40%-70% polyethylene, 10%-33% polypropylene, 5%-10% EPDM rubber, 6%-10% EPDM rubber, 1%-3% release agent, and 2.5%-3.5% cross-linking agent; The preparation method of the polyolefin composition comprises: Mixing polyethylene, EPDM rubber, EPDM rubber, and some additives except the release agent, mixing, kneading, and extruding to obtain a first semi-finished product; The first semi-finished product, polypropylene, paraffin oil, and the remaining additives except the release agent are mixed and extruded to obtain a second semi-finished product; The second semi-finished product is mixed with oleamide and extruded.

2. The polyolefin composition according to claim 1, characterized in that The mass ratio of the paraffin oil to the oleic acid amide is 1:0.1-0.

5.

3. The polyolefin composition according to claim 1, characterized in that The mass ratio of the polyethylene, the polypropylene, the EPDM rubber, the EPDM rubber and the release agent is 20-40:3-33:1.5-10:2-10:

1.

4. The polyolefin composition according to claim 1, characterized in that The feed mass ratio of the EPDM rubber to the EPDM rubber is 0.8-1:

1.

5. The polyolefin composition according to claim 1, characterized in that In terms of mass percentage, the raw materials also include 2%-3% antioxidant and 0.4%-0.6% pigment.

6. The polyolefin composition according to any one of claims 1 to 5, characterized in that The polyethylene is a linear low-density polyethylene with a melt index of 0.1-1 g / 10 min, wherein the melt index is measured at a temperature of 190° C. and a load of 2.16 kg.

7. The polyolefin composition according to any one of claims 1 to 5, characterized in that The polypropylene is a homopolymer polypropylene with a melt index of 0.5-3 g / 10 min, wherein the melt index is measured at a temperature of 230° C. and a load of 2.16 kg.

8. The polyolefin composition according to any one of claims 1 to 5, characterized in that The Mooney viscosity of the EPDM rubber is 10-50, wherein the Mooney viscosity is measured under the conditions of ML1+4 and 100°C.

9. The polyolefin composition according to any one of claims 1 to 5, characterized in that The EPDM rubber is a copolymer of ethylene, propylene and non-conjugated diene. Based on the total mass of ethylene, propylene and non-conjugated diene, the non-conjugated diene accounts for 3%-6%.

10. The polyolefin composition according to claim 5, characterized in that The antioxidant is a complex of antioxidant 1010, antioxidant DLTP, antioxidant 168 and metal ion passivator, the metal ion passivator includes antioxidant 1024 and / or antioxidant XL-1, and the feeding mass ratio of the antioxidant 1010, the antioxidant DLTP, the antioxidant 168 and the metal ion passivator is 1:0.5-0.7:0.5-0.7:0.3-0.

4.

11. The polyolefin composition according to claim 1, characterized in that The crosslinking agent is triallyl isocyanurate and / or trimethylolpropane trimethacrylate.

12. A method for preparing a polyolefin composition according to any one of claims 1 to 11, characterized in that: The preparation method comprises: (1) mixing polyethylene, EPDM rubber, EPDM rubber, and some additives except the release agent, kneading, and extruding to obtain a first semi-finished product; (2) mixing the first semi-finished product, polypropylene, paraffin oil, and the remaining additives except the release agent, and extruding the mixture to obtain a second semi-finished product; (3) mixing the second semi-finished product and oleic acid amide and extruding; Wherein, in step (1), the temperature of the banburying is 140-160°C, the extrusion is carried out by twin-screw and single-screw extrusion granulation, the temperature of the twin-screw is 110-150°C, and the temperature of the single-screw is 110-140°C; In step (2) and step (3), the extrusion is performed by twin-screw extrusion, and the temperature of the twin-screw is 120-200°C.

13. Use of the polyolefin composition according to any one of claims 1 to 11 in preparing an insulation layer for a photovoltaic cable.

Citation Information

Patent Citations

  • Low-odor insulating material suitable for irradiation crosslinked automotive wire as well as preparation method and application of low-odor insulating material

    CN109233055A

  • Silane self-crosslinking low-smoke halogen-free flame-retardant polyolefin oil-resistant elastomer material, and preparation method and application thereof

    CN113956577A